2021
DOI: 10.1155/2021/9752592
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ningmitai Capsules in Patients with Chronic Epididymitis: A Prospective, Parallel Randomized Controlled Clinical Trial

Abstract: Objectives. To evaluate the efficacy and safety of Ningmitai (NMT) capsules in patients with chronic epididymitis. Methods. This prospective randomized controlled trial included 112 patients diagnosed with chronic epididymitis. The patients were randomized (1 : 1 : 1) to receive levofloxacin (LVX), NMT, or NMT combined with LVX for 4 weeks. The patients were followed up at 2 and 4 weeks after initiation of treatment and were evaluated in terms of Chronic Epididymitis Symptom Index (CESI) scores, epididymal nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…NMT capsules have been widely used as a pharmacologic therapeutic method for CP/CPPS in the clinic. Some recently published RCTs have reported that NMT capsules can significantly improve pain symptoms and the quality of life of patients with CP/CPPS [35] and chronic epididymitis [36], and this is consistent with the findings from our study.…”
Section: Discussionsupporting
confidence: 93%
“…NMT capsules have been widely used as a pharmacologic therapeutic method for CP/CPPS in the clinic. Some recently published RCTs have reported that NMT capsules can significantly improve pain symptoms and the quality of life of patients with CP/CPPS [35] and chronic epididymitis [36], and this is consistent with the findings from our study.…”
Section: Discussionsupporting
confidence: 93%
“…33,34,35 However, the use of gabapentinoids is being challenged as it lacks favourable robust evidence for e cacy against pain syndromes other than bromyalgia, post herpetic neuralgia and diabetic neuropathy, and many clinicians have also highlighted the potential for misuse and developing dependence. 36,37,38 The use of BTX-A, Ketamine, Ningmitai and THC for the management of various chronic pain conditions is popular and well established [39][40][41][42][43] and our study shows the effective use of these as analgesics when compared to placebo. There is evidence to support the e cacy of BTX-A for the management of neuropathic pain although the sample sizes used in the studies were small and therefore the real-world applicability remains limited.…”
Section: Discussionmentioning
confidence: 66%